2014
DOI: 10.1007/s00262-014-1578-z
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photopheresis (photochemotherapy) in the treatment of acute and chronic graft versus host disease: immunological mechanisms and the results from clinical studies

Abstract: Extracorporeal photopheresis (ECP) is an immunomodulatory alternative for treatment of graft versus host disease (GVHD). The blood is then separated into its various components through apheresis; buffy coat cells are thereafter treated with 8-methoxypsoralen before exposure to ultraviolet light and finally reinfused into the patient. There is a general agreement that this treatment has an anti-GVHD effect, but the mechanisms of action behind this effect are only partly understood. However, altered maturation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 104 publications
0
31
0
4
Order By: Relevance
“…While the mechanisms by which ECP results in clinical improvement are not completely known, it is thought that ECP can suppress alloimmune responses in part by altering the maturation and function of dendritic cells and through the induction of Tregs. 79 Regardless of the mechanism, responses in chronic GVHD patients have been associated with increased Treg cell counts, increased cellular activation, and inhibition of Tcon. 80,81 ECP has been evaluated in a phase 2 prospective randomized trial, with demonstrated efficacy in sclerodermatous chronic GVHD, including a reduction in steroid dose, meaningful decrease in skin sclerosis, and nonblinded investigator assessment of skin complete or partial responses.…”
Section: Inhibition Of Cytokine Receptor-mediated Signalingmentioning
confidence: 99%
“…While the mechanisms by which ECP results in clinical improvement are not completely known, it is thought that ECP can suppress alloimmune responses in part by altering the maturation and function of dendritic cells and through the induction of Tregs. 79 Regardless of the mechanism, responses in chronic GVHD patients have been associated with increased Treg cell counts, increased cellular activation, and inhibition of Tcon. 80,81 ECP has been evaluated in a phase 2 prospective randomized trial, with demonstrated efficacy in sclerodermatous chronic GVHD, including a reduction in steroid dose, meaningful decrease in skin sclerosis, and nonblinded investigator assessment of skin complete or partial responses.…”
Section: Inhibition Of Cytokine Receptor-mediated Signalingmentioning
confidence: 99%
“…The final mediator of immune tolerance is represented by a CD4+ lymphocyte subpopulation, namely, T‐regulatory cells (T‐reg) . The relevant role exerted by T‐regs has been confirmed by clinical observations .…”
mentioning
confidence: 95%
“…Among treatments for steroid refractory graft‐versus‐host disease (GVHD), extracorporeal photopheresis (ECP) has shown efficacy and tolerability compared to other second‐line immunosuppressive treatments . ECP is considered an immunomodulatory, rather than immunosuppressive, treatment and is not associated with significant increase in opportunistic infections nor disease relapse …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First-line treatment for grade II–IV aGVHD is high-dose steroids (15), and a complete response is observed in 20–40% of patients (16, 17). There is no consensus regarding the preferred therapy for steroid-refractory aGVHD; commonly utilized options include TNFα blockade, anti-IL-6 antibodies, mTOR inhibitors, mycophenolate mofetil, and extracorporeal photopheresis (18). Despite several therapeutic alternatives, patients with grade IV steroid-refractory aGVHD have a dismal long-term prognosis (15).…”
Section: Asct and Gvhdmentioning
confidence: 99%